Growth and attaining global competitive advantage : a study of HINDALCO - Parashar, S. P.; Salwan, Prashant (London : NeilsonJournals Publishing, 2010)
HINDALCO, India's largest Aluminum (Al) and Al product manufacturing company, became the world's 5th largest Al company in FY 2006-07. A decade earlier, it ranked 18th. The growth was both organic and inorganic. Mr. Kumar Manglam Birla, soon after taking over as Chairman after the demise of his father in 1995, crafted a group strategy which aimed at sustaining cost advantage, capitalizing on India's factors of production advantages, and pursuing global value chain opportunities. His strategy initially comprised restructuring, and consolidation. In 2004, Mr. Birla declared, "by and large, the restructuring phase is behind us. Now the focus is on growth. And growth is always more exciting". HINDALCO acquired two bauxite mines in Australia in FY 2004-05 and Novelis in FY 2006-07. But domestic and international competition continued to rise. This lead Mr. Birla to consider what he should do next? Would his strategies of 2001-07 work in the future? What should be done to sustain HINDALCO's competitive advantage?
Originally Published InParashar, S. P., & Salwan, P. (2010). Growth and attaining global competitive advantage: A study of HINDALCO. Journal of International Business Education, 5(1), 75-96. JIBE5-0CS4.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Birla, Kumar Manglam; Hindalco Industries; Aluminum industry and trade -- India; Strategic planning; Business logistics; Organizational effectiveness